Dimensions of comparative religion: Muslim’s perspective - Mohd Amin, Wan Mohd Azam; Rashid, Ungaran; Ahmad, Masitoh; Mohd Nor, Nur Suriya (AHAS KIRKHS, 2024)
This book is an edited book that deals with religions in Malaysia, Islam, Christianity, Judaism, Buddhism and others from the Muslims" perspective. There are ten chapters that originally were written as articles and published in al-liqün: Journal of Islamic Sciences and Comparative Studies, one of the academic journals of International Islamic University of Malaysia. They are reedited and republished with some modifications so that the readers can focus on cach religion respectively. The targeted readers of this book are the students of IIUM who are majoring or minoring in the field of Comparative Religion, that include the subjects of the Study of Religion, Islamic Philosophy, Evengelisation, Islamic Da'wah, Islamic "Aqidah, Textual and Biblical Study of Scriptures and others.